Selection for Upland Rice Varieties Under Different Levels of Light Intensity - Raumjit Nokkoul; Karnchanaporn Unsup; Apichart Krutsuwan; Thirayut Wichitparp (Journal of Experimental Biology and Agricultural Sciences, 2022)
Upland rice varieties were selected under varying levels of light intensity. This study identified shade-tolerant upland rice varieties with a high yield. From November 2016 to March 2017, the experiment was conducted at King Mongkut's Institute of Technology in Ladkrabang, Prince of Chumphon, Thailand. For this, ten varieties of upland rice i.e. Dawk Pa-yawm, Nangdam, Dokkam, Nangchuan, Lebnokrai, Samduen, Maepeung, Damgatondom, Lebmuenang, Pukaotong were grown at different levels of 0%, 50%, 60%, and 70% shading levels. The experiment was conducted in a randomized complete block design with four replications. The results of qualitative characteristics indicated that shadowing conditions didn’t have any significant effect on plant height, 50% flowering age, harvesting age, and panicle length. On the other hand, shaded conditions have a substantial effect on the number of plants per tiller, the number of panicles per tiller, the number of perfect grains per panicle, and the amount of empty grain per panicle since there was a quantitative character. Among the tested varieties, Lebmuenang, Pukaotong, Damgatondom, and Nangchuan varieties are suited for growing under 50% shade conditions while Samduen was only suited for cultivation in 70 % shaded conditions, whereas Pukaotong was good for growing in 50% and 60% shade situations. The results of this experiment did not encourage farmers to use the other varieties as cultivars under shaded conditions due to low yields. However, the outcomes of this study can be used as a reference for breeding programs in low-light conditions.
Keywords: Rice Cultivation and Yield Improvement; GABA and Rice Research; Agriculture, Soil, Plant Science